2005
DOI: 10.1016/j.jacc.2005.02.089
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Asymptomatic Adults With Elevated Coronary Calcium Scores With Atorvastatin, Vitamin C, and Vitamin E

Abstract: Treatment with alpha-tocopherol, vitamin C, and low doses of atorvastatin (20 mg once daily) did not affect the progression of coronary calcification. Treatment may have reduced ASCVD events, especially in subjects with calcium scores >400, but these effects did not achieve conventional levels of statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(88 citation statements)
references
References 27 publications
(20 reference statements)
2
85
0
1
Order By: Relevance
“…27,28 In a randomized controlled trial, a trend toward reduction of cardiovascular events was observed in patients with CAC scores >400 who were treated with statins in combination with antioxidant vitamins. 29 Although our study reflects true daily practice and included consecutive patients, we have to acknowledge several limitations. The observational design remains a major limitation of the current study as end points were not prespecified.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In a randomized controlled trial, a trend toward reduction of cardiovascular events was observed in patients with CAC scores >400 who were treated with statins in combination with antioxidant vitamins. 29 Although our study reflects true daily practice and included consecutive patients, we have to acknowledge several limitations. The observational design remains a major limitation of the current study as end points were not prespecified.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggest that CAC influences physicians' management of CAD risk factors. 233 Although an exploratory subgroup analysis from a single randomized, clinical trial suggests that statin therapy in asymptomatic patients with CAC >400 may improve outcomes, 234 no dedicated, prospective studies have been performed to suggest that the detection of subclinical CAD by CAC leads to improvement in clinical events.…”
Section: Subclinical Cad Assessmentmentioning
confidence: 99%
“…Many studies, which have examined gender differences among family-caregivers, have concluded that women spend more time in providing care and carry out personal-care tasks more often than men. This gender bias influences women to assume more substantial caregiving duties (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, almost an equal number of studies have not found any differences between men and women on these aspects (1,25,28). We found that companion female had more diseases of the musculoskeletal system and connective tissue (44% vs. 21% in male companions; p=0.024), and they were taking more medications of the musculoskeletal system (26.2% vs. 5.4% in male companions; p=0.014), but we found no difference in diseases or treatments about mental health (Table 1).…”
Section: Discussionmentioning
confidence: 99%